2013
DOI: 10.1155/2013/678159
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Inflammation: Epidemiology, Risk Factors, and Markers of Inflammation

Abstract: Obesity is a public health problem that has reached epidemic proportions with an increasing worldwide prevalence. The global emergence of obesity increases the risk of developing chronic metabolic disorders. Thus, it is an economic issue that increased the costs of the comorbidities associated. Moreover, in recent years, it has been demonstrated that obesity is associated with chronic systemic inflammation, this status is conditioned by the innate immune system activation in adipose tissue that promotes an inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
280
3
16

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 380 publications
(309 citation statements)
references
References 186 publications
10
280
3
16
Order By: Relevance
“…This agrees with findings among overweight and obese individuals that display elevated levels of inflammation due to the release of cytokines from adipose tissue [35]. The addition of a quinoa extract rich in 20-hydroxyecdysone to the high fat diet reversed the expression of inflammatory cytokines to levels associated with a low fat diet.…”
Section: Effects On Weight Gainsupporting
confidence: 89%
“…This agrees with findings among overweight and obese individuals that display elevated levels of inflammation due to the release of cytokines from adipose tissue [35]. The addition of a quinoa extract rich in 20-hydroxyecdysone to the high fat diet reversed the expression of inflammatory cytokines to levels associated with a low fat diet.…”
Section: Effects On Weight Gainsupporting
confidence: 89%
“…Our results indicated the inflammation development in rats with MSGinduced obesity. It should be noted that in the case of obesity, chronic low-grade inflammation, which comes out in increased levels of acutephase proteins and pro-inflammatory mediators in blood serum [18], plays a critical role in the development of cardiovascular dysfunction [19], insulin resistance and type II diabetes [7,20].…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, it has been demonstrated that obesity is associated with chronic systemic inflammation, this status is conditioned by the innate immune system activation in adipose tissue that promotes an increase in the production and release of pro-inflammatory cytokines that contribute to the triggering of the systemic acute-phase response [5].…”
Section: Obesity and Inflammation:-mentioning
confidence: 99%